Clustering chemical data set using fuzzy gath-geva algorithm [electronic resource] - 452129 Mahamat Issa Hassan (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2007